2022
DOI: 10.3389/fnut.2022.871521
|View full text |Cite
|
Sign up to set email alerts
|

Gadus morhua Eggs Sialoglycoprotein Prevent Estrogen Deficiency-Induced High Bone Turnover by Controlling OPG/RANKL/TRAF6 Pathway and Serum Metabolism

Abstract: In recent years, the development of safe and effective anti-osteoporosis factors has attracted extensive attention. In this study, an estrogen-deficient osteoporosis rat model was employed to study the improving mechanism of sialoglycoprotein isolated from Gadus morhua eggs (Gds) against osteoporosis. The results showed that compared with OVX, Gds ameliorated the trabecular microstructure, especially the increased trabecular thickness, decreased trabecular separation, and enhanced the trabecular number. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…All kits were operated according to the manufacturer’s instructions. Relative gene expression was standardized to GAPDH by the 2 −ΔΔCT method [ 20 , 21 ]. The relevant primers information is supplemented in the additional document ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…All kits were operated according to the manufacturer’s instructions. Relative gene expression was standardized to GAPDH by the 2 −ΔΔCT method [ 20 , 21 ]. The relevant primers information is supplemented in the additional document ( Supplementary Table S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Xia et al reported that sialoglycoproteins isolated from the eggs of Carassius auratus exhibited anti-osteoporotic activity through increasing the OPG/RANKL ratio [12]. Zhao et al reported that Gadus morhua eggs' sialoglycoprotein prevents high bone turnover by controlling the OPG/RANKL/TRAF6 pathway [14].…”
Section: T-es Reduced Bone Resorption-related Parameters In Serum And...mentioning
confidence: 99%
“…Moreover, the structure of sialoglycoprotein/sialoglycopeptide was distinguished between the various fish species, showing the specific carbohydrate chain, peptide chain, glycopeptides bone, and the kinds of sialic acids. Several studies also proved that sialoglycoprotein/sialoglycopeptide from fish eggs exhibited anti-osteoporosis activities [12,14].…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have reported that G. morhua eggs could reduce bone resorption, increase the bone turnover rate, and effectively improve osteoporosis through the OPG/RANKL signaling pathway. 7 Hei et al isolated a novel sialoglycopeptide from G. morhua eggs that could significantly raise the proliferation activity of MC3T3-E1 cells, increase the content of phosphorus and calcium in rat tibia, and promote longitudinal bone formation in vivo . 8 Our previous results showed that G. morhua peptide (GMP) could inhibit RANKL-induced osteoclast activity and reduce the occurrence of bone resorption, showing strong anti-osteoporotic activity in vivo .…”
Section: Introductionmentioning
confidence: 99%